The feasibility of a randomized controlled crossover trial to assess the effect of probiotic and prebiotic supplementation on the health of elite wheelchair athletes - Anneke Hertig-Godeschalk; Marija Glisic; Belinda Ruettimann; Ezra Valido; Simona Capossela; Jivko Stoyanov; Joelle L. Flueck (Pilot and Feasibility Studies, 2023)
Abstract Background Gastrointestinal (GI) problems represent a health burden in Para athletes and can ultimately reduce athletic performance. This study aimed to evaluate the feasibility of a randomized controlled crossover trial (RCCT) assessing the effects of probiotic and prebiotic supplementation on the health of Swiss elite wheelchair athletes. Methods The RCCT was conducted between March 2021 and October 2021. Athletes were randomized to receive either a daily probiotic (3 g of probiotic preparation, including eight bacterial strains), or a daily prebiotic (5 g of oat bran) supplementation first. After the first supplementation phase (4 weeks), a washout period (4 weeks) and the second crossover supplementation phase (4 weeks) followed. Data were collected at four study visits (every 4 weeks) and included 3-day training and nutrition diaries, the Gastrointestinal Quality of Life Index (GIQLI) questionnaire, stool samples, and fasting blood samples. The study assessed the feasibility criteria such as recruitment rate, retention rate, success of data collection, adherence to the protocol, willingness to participate, and safety. Results This pilot study met the majority of the predefined minimum requirements for the feasibility criteria. Out of 43 invited elite wheelchair athletes, 14 (33%) consented (mean (standard deviation) age: 34 (9) years, eight females, 11 with a spinal cord injury). The desired sample size was not reached, but the achieved recruitment rate was modest, especially considering the population studied. All participating athletes completed the study. With the exception of one missing stool sample and two missing diaries, data were successfully collected for all athletes at all four visits. Most athletes adhered to the daily intake protocol for at least 80% of the days, both for probiotics (n = 12, 86%) and prebiotics (n = 11, 79%). Ten (71%) athletes would be willing to participate in a similar study again. No serious adverse events occurred. Conclusion Despite the limited number of elite wheelchair athletes in Switzerland and the modest recruitment rate, the implementation of a RCCT in elite wheelchair athletes is feasible. The data collected in this study provide essential information for the design of the subsequent study which will include a larger cohort of physically active wheelchair users. Trial registration Swiss Ethics Committee for Northwest/Central Switzerland (EKNZ), 2020–02337). ClinicalTrials.gov, NCT04659408.